Effectiveness of PBL Learning Model with Letter Card Interactive Media Approach in Improving Reading Skills of Grade II Learners in Elementary School - Azzahra, Tasya Nur; Fatayan, Arum (FIP Unimed, 2024)
Elementary schools still have many problems, such as the need for more effectiveness in using models and media to improve reading skills. This study aims to determine the efficacy of a problem-based learning model with a letter card interactive media approach in enhancing the reading skills of grade II students. Type of research: Pre-experiment with a quantitative approach. The research design is One Group Pretest-Postest. The population of this study was all grade II students; 28 students of class II A were selected using the nonprobability sampling technique, a purposive sampling approach. Pre-tests and post-tests were given to determine the level of reading skills. The data collected was processed by paired sample t-test and effect size because the data was expected. This study concludes that using a problem-based learning model with a letter card interactive media approach is practical enough to improve reading skills in grade II. The sig value. 0.000 <0.05 indicates a difference before and after treatment, and the effect size test result is 0.298 with a reasonably effective category. Therefore, it is stated that the initial hypothesis is rejected, and the alternative hypothesis is accepted.Keywords: Problem Based Learning, Letter Card, Reading Skills